2019
DOI: 10.1080/10410236.2019.1567439
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias in Clinicians’ Communication about Human Papillomavirus Vaccination

Abstract: National guidelines recommend human papillomavirus (HPV) vaccination for all 11-12-year-olds, but uptake among United States adolescents remains low. A major barrier to greater uptake is the lack of effective recommendations for HPV vaccine from clinicians. One potential influence on clinicians' recommendations for HPV vaccine that has been relatively unexplored is that of cognitive biases, or errors in judgement that result from 'mental shortcuts' used to make decisions under uncertainty. Therefore, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition to knowledge about the vaccines, personal beliefs and biases can influence provider recommendation practices, both consciously and subconsciously. Cognitive biases, mental shortcuts that can result in errors in uncertain situations, have also been proposed as a framework for understanding HCP hesitancy (Hansen et al, 2020 ; Niccolai & Pettigrew, 2016 ). In a qualitative study, clinicians discussed how the anticipation of an uncomfortable discussion around the HPV vaccine or perceptions about the lack of urgency for the HPV vaccine influenced decisions either to delay recommending the vaccine or to recommending the vaccine less enthusiastically, examples of optimism bias and present bias (Hansen et al, 2020 ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to knowledge about the vaccines, personal beliefs and biases can influence provider recommendation practices, both consciously and subconsciously. Cognitive biases, mental shortcuts that can result in errors in uncertain situations, have also been proposed as a framework for understanding HCP hesitancy (Hansen et al, 2020 ; Niccolai & Pettigrew, 2016 ). In a qualitative study, clinicians discussed how the anticipation of an uncomfortable discussion around the HPV vaccine or perceptions about the lack of urgency for the HPV vaccine influenced decisions either to delay recommending the vaccine or to recommending the vaccine less enthusiastically, examples of optimism bias and present bias (Hansen et al, 2020 ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
“…Cognitive biases, mental shortcuts that can result in errors in uncertain situations, have also been proposed as a framework for understanding HCP hesitancy (Hansen et al, 2020 ; Niccolai & Pettigrew, 2016 ). In a qualitative study, clinicians discussed how the anticipation of an uncomfortable discussion around the HPV vaccine or perceptions about the lack of urgency for the HPV vaccine influenced decisions either to delay recommending the vaccine or to recommending the vaccine less enthusiastically, examples of optimism bias and present bias (Hansen et al, 2020 ). Similar findings have been confirmed in quantitative studies—two national surveys of pediatricians found that about one third of respondents anticipated uncomfortable conversations about the HPV vaccine and one found that about half of respondents did not recommend same day vaccination for the HPV vaccine (Gilkey et al, 2015 ; Kempe et al, 2019 ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive biases undermine many health decisions, including vaccination decisions of adults and parents of adolescents. [18][19][20] The principles of behavioral economics have been used to understand how cognitive biases impact health behaviors, such as vaccination, and to shift such behaviors toward improved health outcomes. 1 Behavioral economics is a strategy to help overcome cognitive biases and encourage vaccination, especially for recommended vaccines that do not benefit from mandates.…”
mentioning
confidence: 99%